The Relationship Between Learning Motivation and Learning Achievement Learners at SMA Negeri 1 Nita - Wi, Antonia Wisang (Jurnal Riset Ilmu Pendidikan, 2022)
The purpose of this study is to find out the relationship between learning motivation and learning achievements of students at SMA Negeri 1 Nita. This research was conducted at SMA Negeri 1 Nita. The population of this study amounted to 123 learners. Sample of 55 learners. The instrument consists of a questionnaire. Validation of this research is using the Person Product Moment formula through the SPSS v. 23 for window program. Data analysis techniques use quantitative descriptive correlation. After the data is dispersed. The results of the analysis of research data showed that the correlation coefficient value of 0.461 was marked positive or unidirectional, then obtained the value of p = 0.000 correlation or the relationship between the two variables was significant either at the level of 0.05. This can be seen from the existence of correlation coefficient numbers. The value is compared to rtabel at a significant level of 5% for N = 55 obtained the number 0.266 and it is seen that rhitung> rtabel or 0.461 > 0.266, so that the null hypothesis (H0) is rejected and Hypotension (H1) is accepted. This means that there is a positive and significant relationship of emotional independence with the learning motivation of SMA Negeri 1 Nita students.